Discipline of Middle and High School Level Children during Evening Study Hours - Tasijawa, Budawan (Jurnal Pendidikan Amartha, 2023)
Education is an effort to prepare the necessary human resources that can be realized, and cannot be separated from human life, because it is absolute both in the life of individuals, families, communities and in the life of the nation and state. Education is a process of humanizing humans from the time they happened until the end of their lives through various knowledge which is conveyed in the form of teaching in stages, where the teaching process becomes the responsibility of parents and society towards approaching oneself to God so as to become a perfect human being. The purpose of this study was to find out: 1. To find out the Discipline attitude of Middle and High School Level Children at Night Study Hours in Walnewen Hamlet, Waspait Village, Fena Leisela District, Buru Regency. 2. To find out how Children Discipline During Night Study Hours in Walnewen Hamlet, Waspait Village, District Fena Leisela, Buru Regency. 3. To find out the driving and inhibiting factors that are experienced in the Discipline of Middle and High School Level Children during Night Study Hours in Walnewen Hamlet. Type of research. This study uses a qualitative descriptive method, namely to reveal the Discipline of Middle and High School Level Children at Night Study Hours in Walnewen Hamlet, Waspait Village, Fena Leisela District, Buru Regency and the approach used in this research is a qualitative approach to find out or describe the reality of the problems researched. The data analysis technique used in this study is to use the steps as stated, namely as data collection is an integral part of data analysis activities. Data collection activities in this study were conducted using interviews and documentation studies. Research Results Based on observational data, interviews and documentation carried out in this study were to collect information related to the Discipline of Middle and High School Level Children in Evening Study Hours. Walnewen Hamlet, Waspait Village, Fena Leisela District, Buru Regency, will discuss the findings of the following researchers.